Comparative In-vitro Efficacy of Selected Fungicides and Plant Extracts for the sustainable management of Sugarcane Red Rot Caused by Colletotrichum falcatum (Journal of Agriculture and Veterinary Science, 2026)
Sugarcane (Saccharum officinarum L.) is one of the economically valuable crops grown worldwide, but its production is severely affected by red rot caused by Colletotrichum falcatum. Therefore, the present study evaluates integrative approaches for the management of Colletotrichum falcatum. In this study, five fungicides, and five botanical extracts were tested against C. falcatum under in-vitro conditions using the poisoned food technique in a Completely Randomized Design (CRD) with three replications. According to results, chemical treatments, Propineb + Iprovalicarb, Pyraclostrobin + Metiram, and Thiophanate methyl at 300 ppm almost completely inhibited mycelial growth, while garlic extract at 15% was the most potent botanical, completely suppressing fungal growth. These findings demonstrate that effective fungicides, and potent plant extracts can significantly reduce C. falcatum growth, suggesting their potential use in integrated and sustainable management of red rot in sugarcane.